Optimal control of continuous ozonation of non-biodegradable pollutants. (June 2018) - Al Jibouri, Ali Kamel H.; Upreti, Simant R.; Wu, Jiangning
Highlights: The ozonation of naphthenic acids (NAs) in industrial wastewater was optimally controlled. The best optimal control policy of ozone/oxygen gas flowrate vs time minimized NAs concentration with lowest gas consumption. The wastewater thus treated contained only rapid biodegradable organic substances with more than 92% of the toxicity removed. Abstract: In this study, optimal control is applied for the first time to a continuous ozonation process for the removal of recalcitrant, non-biodegradable pollutants from industrial wastewater. Naphthenic acids (NAs) is used as a model pollutant because it is a major source of pollution in the oil and oil sands industries. Using ozone/oxygen gas flowrate versus time as the control function in a rigorous process model, the necessary conditions are derived to minimize NAs concentration in the wastewater. A computational algorithm is utilized to solve the necessary conditions, and yield the optimal control policies based on different initial guesses. The optimal policy that has minimum gas consumption is identified and experimentally validated. The results demonstrate that this policy minimizes NAs concentration in the wastewater to 13.5% of the original value. An absolute difference of 3.08% is attained between the predicted objective functional, and its experimental counterpart obtained by implementing the optimal policy. The treated wastewater is found to be rapidly biodegradable with 92.77% of the toxicity removed.